PENGARUH RIWAYAT INFEKSI DAN ASI EKSKLUSIF TERHADAP TUMBUH KEMBANG BALITA DALAM MENCEGAH STUNTING - Elvalini Warnelis Sinaga; Debora Simamora (Universitas Prima Indonesia, 2021)
Stunting is a condition where the toddler's height is less than normal, this is an important problem for Indonesia today. The research method used naturalistic phenomenology with a retrosfective study approach. location in the Kelurahan Pekan Labuhan Medan., a total sample of 50 people, questionnaire interview research instruments. The results showed that there was an effect of infection history and exclusive breastfeeding on toddler growth and development. The results of the statistical analysis of the T test showed that the history of infection had an influence on the growth and development of children under five (p = 0.01; p <0.05), exclusive breastfeeding had an effect (p = 0.02; p <0.05) on the growth and development of children under five. Suggestions for further research with a different design.